2015
DOI: 10.1007/s00520-014-2584-6
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors related to arm weakness in patients with breast cancer-related lymphedema

Abstract: Appropriate physical and psychological interventions, including providing accurate information and reassurance of physical activity safety, are necessary to prevent arm weakness and physical dysfunction in patients with breast cancer-related lymphedema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
2
18
0
1
Order By: Relevance
“…Although some studies reported that there was no difference between arms in patients with lymphedema [12], others claimed that this difference was significantly high [13, 14]. The decrease before treatment in the affected arm was attributed to the relatively lower use of that arm, pain after surgery, lymphedema, accompanying rotator cuff disorders, adhesive capsulitis, neuromuscular disorders, or dermatitis [6, 22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although some studies reported that there was no difference between arms in patients with lymphedema [12], others claimed that this difference was significantly high [13, 14]. The decrease before treatment in the affected arm was attributed to the relatively lower use of that arm, pain after surgery, lymphedema, accompanying rotator cuff disorders, adhesive capsulitis, neuromuscular disorders, or dermatitis [6, 22].…”
Section: Discussionmentioning
confidence: 99%
“…It might be valuable to show a possible weakening of the muscles after CDT. Most of our patients were tentative about using their affected arm, and this situation usually results in muscle atrophy, weakness, and functional restrictions [6]. However, active resistive exercise was found not to increase the volume of the limb and resulted in a decrease of volume in the proximal arm in a study [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were asked about their ability to lift a shopping bag or suitcase in order to assess arm function; however, no relationship was detected between arm/hand swelling and upper limb function in older adults (12). Consistent with the previous studies including mixed-aged populations of breast cancer survivors, we used the DASH questionnaire to assess arm function (3)(4)(5)(6)(7)10,11,13). It has been suggested that DASH score increases an average of 0.3 points yearly in healthy patients, and an expected normative DASH score can be calculated using the following formula: [(0.29×age of subject)−4.46] in women (14).…”
Section: Discussionmentioning
confidence: 99%
“…There are strong associations between shoulder movement deviations, muscle control, patient‐reported pain, chemotherapy, and radiotherapy . In one study, fear of lymphedema and disuse of the affected arm contributed significantly to a difference in muscle strength between the affected and unaffected shoulders of patients . Pain serves to increase muscle activation and is likely to limit movement .…”
Section: Introductionmentioning
confidence: 99%